Nutritional Status Assessment Based on BMI-Age and Metabolic Syndrome Status among Adolescents - Elen Kahi Leba; Margaretha Saurmalis Pandiangan; Gracentya Marsella Pertiwi Anin; Gelora Mangalik; Dary Dary (GLOBAL HEALTH SCIENCE GROUP, 2025)
Adolescents are in a transitional phase that often involves changes in dietary habits and lifestyle, which can significantly affect their nutritional status and increase the risk of metabolic syndrome. This study aimed to identify the nutritional status based on Body Mass Index-for-Age (BMI/A) and metabolic syndrome status among adolescents in Semarang Regency. A quantitative descriptive survey with a cross-sectional approach was conducted at SMA Negeri 1 Pabelan, Semarang Regency, from March to July 2024. A total of 86 students aged 16–18 years were selected using random sampling. Data collection included anthropometric measurements (height, weight, waist circumference) to assess nutritional status and blood tests for glucose, uric acid, and cholesterol levels to identify potential metabolic syndrome. Data analysis was conducted using quantitative descriptions. The results showed that 11.6% of respondents were undernourished and 8.1% were obese. The prevalence of pre-metabolic syndrome was higher among female students (33.7%) compared to male students (16.3%), while metabolic syndrome was more common among males (27.9%) than females (18.6%). In conclusion, most adolescents had a good nutritional status; however, the presence of undernutrition and obesity indicates a risk of metabolic syndrome. Continuous health monitoring and education regarding balanced nutrition and healthy lifestyles are essential to prevent adolescent metabolic disturbances.